Boorin niukkuus raudanpuutostaudin aiheuttajana kaurassa rahkasuolla - Heinonen, Reijo (Agricultural and Food Science, 1961)
A series of minor element deficiencies was observed in oats on a newly reclaimed sphagnum peat in Kiikala, SW Finland. Firstly, a copper deficiency caused a complete failure of the crop and an analysis revealed a copper content of less than 1 pmm in the unsound straw. After an application of copper sulphate (50 kg/ha), a severe iron chlorosis appeared, which damaged the crop except on ditch-sides where sand had been spread. Analyses of chlorotic and healthy plants and corresponding soil samples are given in Tables 1 and 2. The principal problem was, however, a boron deficiency, which prevented normal development of roots. The roots of the chlorotic plants were weak, brownish, with many short and thickened branches (symptoms identical with those recently described by KORONOWSKI) . An application of boron (in connection with lime, NPK and Cu) made possible a normal root development which in turn enabled the plants to make use of the scanty supply of iron in a greater volume of soil, and to produce a good crop yield.